PENGARUH PEMAHAMAN AKUNTANSI, SOSIALISASI SAK EMKM DAN PERSEPSI PELAKU UMKM TERHADAP PENERAPAN SAK EMKM - Khoirunnisa, Nabila; Kosadi, Ferry (JURNAL WIDYA, 2025)
This study aims to analyze the effect of accounting understanding, socialization of SAK EMKM, and perceptions of MSME actors on the application of SAK EMKM in MSMEs in Coblong District, Bandung City. The research method used is quantitative method with data collection techniques using a questionnaire. The population in this study were MSME players operating in the Coblong District area of Bandung City, totaling 98 business units, with sampling techniques using Non-Probability Sampling through a saturated sampling approach. Data analysis techniques using multiple linear regression analysis. The results showed that: (1) Accounting understanding has a significant positive effect on the application of SAK EMKM with a regression coefficient of 0.453; (2) Socialization of SAK EMKM has a significant positive effect on the application of SAK EMKM with a regression coefficient of 0.747; (3) Perceptions of MSME actors have a significant positive effect on the application of SAK EMKM with a regression coefficient of 0.360. Simultaneously, the three independent variables have a significant effect on the application of SAK EMKM with an R Square value of 0.878 or 87.8%.